2022
DOI: 10.1371/journal.pone.0263731
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postpartum haemorrhage in the Northern Province of Rwanda: A case control study

Abstract: Background Postpartum haemorrhage (PPH) remains a major global burden contributing to high maternal mortality and morbidity rates. Assessment of PPH risk factors should be undertaken during antenatal, intrapartum and postpartum periods for timely prevention of maternal morbidity and mortality associated with PPH. The aim of this study is to investigate and model risk factors for primary PPH in Rwanda. Methods We conducted an observational case-control study of 430 (108 cases: 322 controls) pregnant women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 60 publications
(107 reference statements)
4
26
3
1
Order By: Relevance
“…which revealed that women in urban areas use contraception more than those in rural areas, possibly due to more exposure to numerous streams of information, proximity to health services, and easier access to a wider range of methods to choose from. This study's findings, however, confirm those of a prior study [ 1 ], which revealed that contraceptive use is highest in the Northern region of Rwanda, despite a primarily hilly terrain and difficulties in reaching health facilities [ 53 ], most likely due to the region's high presence of non-governmental health organizations that emphasize access to sexual and reproductive health services.…”
Section: Discussionsupporting
confidence: 82%
“…which revealed that women in urban areas use contraception more than those in rural areas, possibly due to more exposure to numerous streams of information, proximity to health services, and easier access to a wider range of methods to choose from. This study's findings, however, confirm those of a prior study [ 1 ], which revealed that contraceptive use is highest in the Northern region of Rwanda, despite a primarily hilly terrain and difficulties in reaching health facilities [ 53 ], most likely due to the region's high presence of non-governmental health organizations that emphasize access to sexual and reproductive health services.…”
Section: Discussionsupporting
confidence: 82%
“…This contradicts prior research [47,48] which revealed that women in urban areas use contraception more than those in rural areas, possibly due to more exposure to numerous streams of information, proximity to health services, and easier access to a wider range of methods to choose from. This study's ndings, however, con rm those of a prior study [1], which revealed that contraceptive use is highest in the North of Rwanda, despite a primarily hilly terrain and di culties in reaching health facilities [49], most likely due to the region's high presence of non-governmental health organizations that emphasize access to sexual and reproductive health services.…”
Section: Resultssupporting
confidence: 79%
“…This vascular triad is a life-threatening condition that predisposes patients to critical obstetric bleeding. Additionally, the present study suggests that this vascular triad is not associated with the occurrence of atonic bleeding, which is another common cause of critical obstetric bleeding [ 27 29 ]. Different mechanisms underlying obstetrical critical bleeding are implied; (1) conditions with vasospasm resulting in the development of aforementioned vascular triad and (2) conditions with other causes bringing atonic postpartum hemorrhage including functional and traumatic causes.…”
Section: Discussionmentioning
confidence: 79%